2017
DOI: 10.3233/bmr-169669
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain symptoms among allied health professions’ students: Prevalence rates and associated factors

Abstract: MPS in AHP students are prevalent and statistically higher among females. Students are advised to adhere to different conservative precautions and follow prevention programs. Future studies are needed to assess actual mechanisms causing MPS among AHP students and designing effective prevention programs specific to AHP students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 55 publications
5
38
1
13
Order By: Relevance
“…Male students most commonly reported MPS in the lower back, the neck and knees. A study performed on allied health profession students in Jordan reported the highest prevalence of MPS in the neck, the lower back, shoulders, and upper back [20]. Similar to the current results where MPS in these areas were more prevalent in females, Jordanian female students were more likely to report a 12-month duration of MPS in the neck, shoulders, wrists and hands, the upper back, and hips/thighs.…”
Section: Musculoskeletal Pain Symptomssupporting
confidence: 82%
See 3 more Smart Citations
“…Male students most commonly reported MPS in the lower back, the neck and knees. A study performed on allied health profession students in Jordan reported the highest prevalence of MPS in the neck, the lower back, shoulders, and upper back [20]. Similar to the current results where MPS in these areas were more prevalent in females, Jordanian female students were more likely to report a 12-month duration of MPS in the neck, shoulders, wrists and hands, the upper back, and hips/thighs.…”
Section: Musculoskeletal Pain Symptomssupporting
confidence: 82%
“…However, higher levels of vigorous-intensity and total PA were also associated with a higher prevalence of MPS which prevented daily activities. Exercise was not associated with any MPS in Jordanian or Saudi Arabia students [20,54]. Furthermore, physical activity was not associated with lower back pain in Saudi Arabia university students of Medical and Health Sciences [57].…”
Section: Musculoskeletal Pain Symptomsmentioning
confidence: 81%
See 2 more Smart Citations
“…A ferramenta utilizada na atual pesquisa foi o questionário Nórdico, instrumento este difundido e traduzido para várias línguas, sendo utilizado por diversos estudos que visam a avaliação dos sintomas dolorosos, sendo também utilizado por outros estudos que analisaram a presença de dor ocupacional (Almhdawi et al, 2017).…”
Section: Discussionunclassified